Screen Time and Physical Activity in Under-Five Children - Rachmania, Diana; Ludyanti, Laviana Nita (Pediomaternal Nursing Journal, 2022)
Introduction: High screen time is defined as activities in front of a screen for more than 60 minutes in 24 hours. These activities can lead to a decreased rate of physical activities in under-five children and pose a risk of turning into gaming addiction or gaming disorder. This study aimed to identify the relationship between screen time and physical activities in under-five children at PAUD Al Azhaar Tulungagung.Method: This study was designed as a correlational study with a cross-sectional approach with a purposive sampling technique. The population in this study was all mothers and children aged 24-60 months at PAUD Al Azhaar Tulungagung totaling 35 people. The number of samples was 31 respondents. The study was conducted at one of PAUD in Tulungagung area. Instruments for collecting data in this study were modified screen time and PAQ-C questionnaires to measure physical activities.Results: The results show that nearly all (83.9%) respondents had high screen time and the majority of them (51.6%) displayed decreased physical activities. An analysis with Spearman's Rank statistical test obtained a p-value of 0.00 <α 0.05, meaning that there is a relationship between screen time and physical activities in under-five children at PAUD Al Azhaar Tulungagung. A correlation coefficient of -0.701 shows that there is a negative (inverse) and strong relationship.Conclusions: Parents play a significant role in directing positive screen time for children and encouraging them to be physically active instead of spending time in front of a screen.